An Exploratory Study on the Drug Utilization Pattern in Glaucoma Patients at A Tertiary Care Hospital - Pooja Prajwal, Mohandas Rai, H N Gopalakrishna, Ramya Kateel (Journal of Applied Pharmaceutical Science, 2013)
Glaucoma is a chronic, progressive optic neuropathy caused by group of ocular conditions which lead to damage of optic nerve with loss of visual function. The objective of the study is to assess the average number of drugs per prescription, formulations being prescribed, various categories of drugs being prescribed and the category most often used in glaucoma patients in ophthalmology. This is a retrospective hospital based study carried out in the department of ophthalmology at A.J institute of medical sciences, Mangalore. The study period was from July 2012 to July 2013. Total number of prescriptions analyzed were 344 , in which total of 1,064 drugs were prescribed. Analysis of the prescriptions showed that average number of drugs per prescription was 3.09. The maximum number of drugs prescribed were in the form of eye drops (76.56%), followed by ointments (12.06%), tablet (4.2%), capsules (3.94%), syrup (2.16%) and injection (1.08%). The dosage form was indicated for 94%, frequency of drug administration for 96% drugs and duration of treatment for only 78% of the drugs prescribed. Around 48.44% of diagnosis accounted for primary open angle glaucoma. Rest 32.96% and 18.6% acconting for angle closure glaucoma and absolute glaucoma respectively. The number of antibiotics prescribed was 600 (56.43%), out of these 413 (68.79%) antibiotics were prescribed in the form of drops, 174 (29.06%) as ointment and 13 (2.15%) orally. Number of encounters with anti-inflammatory and antiallergic drugs was 118 (11.12%), mydriatics and cycloplegics 105 (9.84%), miotics 28 (2.6%), lubricant and miscellaneous eye drops 209 (19.63%) and multivitamins 4 (0.38%). Prescription writing errors were at its minimum thereby avoiding irrational prescriptions. Duration of treatment and prescribing by generic name were very low.
Keywords: Drug utilization, primary open angle glaucoma, angle closure glaucoma, absolute glaucoma, prescription analysis, generic name.